Novel NALCN biallelic truncating mutations in siblings with IHPRF1 syndrome. Issue 6 (5th February 2018) - Angius, A.; Cossu, S.; Uva, P.; Oppo, M.; Onano, S.; Persico, I.; Fotia, G.; Atzeni, R.; Cuccuru, G.; Asunis, M.; Cucca, F.; Pruna, D.; et al.
Abstract : Infantile hypotonia with psychomotor retardation and characteristic facies‐1 (IHPRF1) is a severe autosomal recessive neurologic disorder with onset at birth or in early infancy. It is caused by mutations in the NALCN gene that encodes a voltage‐independent, cation channel permeable to NM, K + and Ca 2+ and forms a channel complex with UNCSO and UNC79. So far, only 4 homozygous mutations have been found in 11 cases belonging to 4 independent consanguineous families. We studied a Sardinian family with 2 siblings presenting dysmorphic facies, hypotonia, psychomotor retardation, epilepsy, absent speech, sleep disturbance, hyperkinetic movement disorder, cachexia and chronic constipation. Polymorphic generalized seizures started at 4 and 6 years, respectively. Anti‐epileptic drugs (AEDs) therapy was efficient for female proband's epilepsy, but the male still has weekly seizures. Whole exome sequencing identified 2 novel truncating mutations in NALCN allowing to assess the clinical phenotype to IHPRF1. This is the fifth family reported worldwide, and these are the first European cases with IHPRF1 syndrome with biallelic truncating mutations of NALCN .